Plasma membrane aquaporins interact with the endoplasmic reticulum resident VAP27 proteins at ER‐PM contact sites and endocytic structures - Fox, Ana Romina (2020)
Plasma membrane (PM) intrinsic proteins (PIPs) are aquaporins facilitating the diffusion of water and small solutes. The functional importance of the PM organization of PIPs in the interaction with other cellular structures is not completely understood. We performed a pull-down assay using maize (Zea mays) suspension cells expressing YFP-ZmPIP2;5 and validated the protein interactions by yeast split-ubiquitin and bimolecular fluorescence complementation assays. We expressed interacting proteins tagged with fluorescent proteins in Nicotiana benthamiana leaves and performed water transport assays in oocytes. Finally, a phylogenetic analysis was conducted. The PM located ZmPIP2;5 physically interacts with the endoplasmic reticulum (ER) resident ZmVAP27-1. This interaction requires the ZmVAP27-1 cytoplasmic major sperm domain. ZmPIP2;5 and ZmVAP27-1 localize in close vicinity in ER/PM contact sites (EPCSs) and endocytic structures upon exposure to salt stress conditions. This interaction enhances PM water permeability in oocytes. Similarly, the Arabidopsis ZmVAP27-1 paralog, AtVAP27-1, interacts with the AtPIP2;7 aquaporin. Together, these data indicate that the PIP2-VAP27 interaction in EPCSs is evolutionarily conserved, and suggest that VAP27 might stabilize the aquaporins and guide their endocytosis in response to salt stress.